ANALISIS ALIH KODE PESERTA DIDIK DALAM KEGIATAN PEMBELAJARAN IPAS - Oktavian, Farhan Athif; Yuliana, Rina; Hamidiyah, Aisyah (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2025)
This study aims to analyze the types of code-switching used by students during Science and Social Studies (IPAS) learning activities and to identify the factors that contribute to its occurrence. The research employed a qualitative approach with a case study method. The subjects were fifth-grade students at SD EvFia Land Serang, a bilingual school that implements English as the primary language of communication. Data were collected through classroom interaction observations, interviews with teachers and the principal, and documentation. The findings reveal that students employed three types of code-switching during IPAS lessons: intra-sentential code-switching (71.67%), tag-switching (16.67%), and inter-sentential code-switching (11.67%). Intra-sentential code-switching was the most dominant form, characterized by language mixing within a single sentence, particularly when students asked questions or explained concepts to the teacher. The factors influencing code-switching include the speaker (33.33%), the interlocutor (22.22%), the presence of a third party (22.22%), and changes in formality levels (22.22%). These findings suggest that code-switching serves as an adaptive communication strategy responding to social and linguistic contexts. Students’ code-switching behavior occurs naturally as part of their efforts to communicate effectively and comprehend lesson content within the bilingual classroom environment.